(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2019)
The objective of this analysis is the phraseological content of the many different dictionary resources that users and translators can consult nowadays. In order to do so, we compare the phraseological content of the different types of dictionaries in use, monolingual and bilingual repositories in paper and in electronic form, dictionaries for PDAs, online, with the phraseological content of the dictionaries developed by teams of linguists, etc. This analysis will make it possible for users to choose the most efficient tools. Finally, we show the possible use of electronic dictionaries to create phraseological and translation applications.